Concordance Between Patient and Physician Assessment of the Magnitude of Peyronie's Disease Curvature. (10th October 2013) - Matsushita, Kazuhito; Stember, Doron S.; Nelson, Christian J.; Mulhall, John P.
Abstract Introduction The magnitude of penile deformity is a critically important factor in Peyronie's disease, as it is associated with increased difficulty in penetrative sexual intercourse and in turn with negative psychosocial consequences. Deformity magnitude also influences treatment choice when surgical correction is indicated. Aim To determine the concordance between patient and physician assessment of magnitude of penile curvature in men with Peyronie's disease. Methods Patient assessment of curvature was obtained at initial interview. Physician assessment was performed using intracavernosal injection‐assisted erection using a goniometer applied during excellent penile rigidity. Main Outcome Measures Patient and physician assessments of penile curvature. Results The sample consisted of 192 men with a mean age of 54 ± 12 years old. Mean curvature on patient and physician assessment was 33 ± 17 and 36 ± 18 degrees, respectively. Only 49% of patients (94) correctly assessed their curvature, whereas 35% underestimated and 16% overestimated it. Conclusions Only half of PD patients accurately assess their penile curvature, with more than twice as many patients underestimating it than overestimating it. These data suggest that patient self‐reporting of penile curvature should not be used as a clinical marker or end point in Peyronie's disease trials. Matsushita K, Stember DS, Nelson CJ, and Mulhall JP. Concordance between patient and physician assessment of the magnitude of Peyronie's disease curvature. J Sex Med 2014;11:205–210.